THE INSTITUTE OF ANTICIPATION OF THE EFFECTS OF PROVISIONAL RELIEF BEFORE THE 2015 CIVIL PROCEDURE CODE REFORM (VERUM: Journal of Scientific Initiation, 2022)
This paper is dedicated to the study of the anticipation of the effects of provisional relief in actions aimed at guaranteeing citizens' right to health. Its objective is to analyze the way the Judiciary is acting in defense of the right to health, particularly with regard to the anticipation of the effects of provisional relief. The issue addressed is: as health is a right for all, how is the Judiciary facilitating access to this right, and what are the requirements for granting provisional relief, specifically in judicial actions related to health? To address this question, a conceptual and historical study of the anticipation of provisional relief is first conducted, prior to the reform of the Civil Procedure Code that occurred in 2015. Subsequently, the fundamental right to health is analyzed in light of constitutional legislation. The methodology used involves bibliographical research, reading, and analysis of relevant legislation, doctrinal works, and support materials published on the internet.
Keywords: Judicialization of Health; Fundamental Right; Provisional Relief